Al Qaeda in Its Third Decade Irreversible Decline or Imminent Victory? - Jenkins, Brian Michael (RAND Corporation, 2012)
This essay examines a number of issues concerning the status of al Qaeda more than ten years after 9/11, including whether America has won the operational battle but lost the ideological contest; whether homegrown terrorism is a growing threat; whether maintaining American troops in Afghanistan is essential; and whether the United States ought to declare on its own an end to the war on al Qaeda.